Rapid climate change, integrated human–environment–historical records and societal resilience in Georgia - Loveluck, Christopher P.; Tielidze, Levan G.; Elashvili, Mikheil; Kurbatov, Andrei V.; Gadrani, Lela; Erb-Satullo, Nathaniel L.; von Suchodoletz, Hans; Dan, Anca; Laermanns, Hannes; Brückner, Helmut; Schlotzhauer, Udo; Sulava, Nino; et al. (MDPI, 2024)
In the midlatitudes of the planet, we are facing the imminent disappearance of one of our best high-resolution (pre)historic climate and anthropogenic pollution archives, namely the loss of glacial ice, through accelerated global warming. To capture these records and interpret these vanishing archives, it is imperative that we extract ice-cores from midlatitude regions where glaciers still survive and analyse them within frameworks of inter-disciplinary research. In this paper, we focus on Georgia, part of the Greater Caucasus. Results of ice-core analyses from the region have never, to date, been integrated with its other abundant palaeo-environmental, archaeological and historical sources. We review the results of international projects on palaeo-environmental/geoarchaeological sediment archives, the archaeology of metal economies and preliminary ice-core data in Georgia. Collectively, we show that the different strands need to be integrated to fully explore relationships between climate/landscape change and human societal transformations. We then introduce an inclusive interdisciplinary framework for ongoing research on these themes, with an ultimate future goal of using data from the past to inform societal resilience strategies in the present.
Keywords: 37 Earth Sciences; 3709 Physical Geography and Environmental Geoscience; 3705 Geology; Climate-Related Exposures and Conditions; 13 Climate Action